Smart Clients versus Web Forms. - Veeramani, Narayan (Computer (00189162), 2006)
The article features the framework that links the gap between Web forms and smart clients. It offers information on the comparison of smart client and Web form's application characteristics which includes response time, ability to work offline, easy deployment, security and paradigm of programming. The applications of smart client have complete access to local file system, registry, and printer while the access of Web forms to local client resources is restricted by the browser security configuration. The Microsoft .NET framework addresses deployment and security concerns to bridge the gap but for mission-critical Web-based applications, companies will continue to prefer Web forms technology.